A quasi-experimental study on the influence of different media scaffolds toward physics problem-solving processes. Issue 2 (17th February 2023) - Zhu, Guangtian; Su, Xiaoling; Du, Juan; Chen, Qingwei; Xiong, Bolong; Chiang, Feng-Kuang
ABSTRACT: Physics is a subject requiring strong logical thinking, and writing a problem-solving path according to logical thinking can enhance students' knowledge and problem-solving ability. The purpose of the study was to explore the effects of problem presentation of different scaffolds (MAPS or dynamic figures) on students' physical problem solving. MAPS scaffold is a modeling applied to problem-solving pedagogy. The study adopts a quasi-experimental design, as participants were divided into four groups tested under different scaffolds. These groups are Traditional group (problems with static figures), MAPS group (MAPS combined with static figures), Dynamic Figure group (problems with dynamic figures), and MAPS + Dynamic Figure group (MAPS combined with dynamic figures). The results indicated that the students assisted by MAPS could more effectively describe and interpret key concepts and knowledge in questions, and they selected formulas appropriately according to the physics conditions. However, the findings did not reveal any significant difference between the dynamic figure. Thus, we will explore dynamic figures in different types of physics questions in future research, so that dynamic figures can be more effectively used by students for physics problem-solving.